Skema Kendali Ball-Balancing Robot Secara Nirkabel - Gunawan Dewantoro; Franciscus Dalu Setiaji; Edwin C. Mone (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
The control system and algorithm of robot keeps developing vigorously nowadays, including that of balancing robot which is an unstable system. And one of those robots is ball-balancing robot which has two degree of freedoms and is the advanced development of the universal two-wheel robots. However, these robots have not taken navigation control into account. These research aims to implement ball-balancing robot with wireless navigation control.The ball-balancing robot is a module which its equilibrium is controlled such that it tends to 0° for both θ as well as ψ angles, using two PID controllers. In addition, PID based speed control of the DC motors are also required. The inclination angle data are acquired by accelerometer and gyroscope simultaneously. The data processing and robot control are processed by ATMega2560 microcontroller. The system testing includes the accuracy of sensors data processing, PID control system, and the motion control of the robot. This control system has been realized but in general still has drawbacks. This robot is still sluggish to respond the changes of set points. This system only moves freely with disturbances up to 7o. This arises from the mechanical design limitation.